Drought Occurrence Pattern in Tigray Region, Northern Ethiopia - A.S. Tefera; J.O. Ayoade; N.J. Bello (Journal of Applied Sciences and Environmental Management)
Drought is characterized using parameters including duration, severity, intensity and spatial coverage. Drought frequency and trend can also be used as additional parameters to further characterize drought occurrences. In this study, drought occurrence was examined using Standard Precipitation and Evapotranspiration Index (SPEI) as an assessment tool. Based on the SPEI results, spatial and temporal patterns were inspected both at district and regional levels. In doing so, monthly climate data collected on selected stations, from the Dutch national weather service known as the Royal Netherlands Meteorological Institute (KNMI), was used to assess the drought trends and characterize the study area in terms of drought duration, severity, intensity, frequency, spatial extent as well as drought trend. The analysis results indicated that most districts in the southern and eastern zones experienced more intense droughts than the rest of the study area. It was also found that the average drought return period in the study area ranged between 2.02 at 3-month, 6-month and 24-month time scales to 2.13 years at 12-month time scale. A statistically significant increasing drought trend was also revealed at all-time scales. Generally, the study has revealed an increasing trend of drought occurrence and spatially variable drought duration, severity, intensity and frequency in the study area. The short return period and increasing drought trends indicate the need for urgent drought management intervention.